The model for improving the manufacturing process in Serbian small-scale production enterprises - Vorkapić, Miloš; Ćoćkalo, Dragan Ž; Sajfert, Dragana; Đorđević, Dejan; Cvijanović, Strahinja (Industrija, 2017)
The paper presents a theoretic model for improving the manufacturing proces that was developed and tested in small-scale production enterprises. The model also represents a new organizational model which enables a complete implementation of pull strategy, insufficiently used in Serbia up to now, with a stress on sustainable manufacturing process, remanufacturing process and environmental protection. The model also includes the guidelines to SMEs - how to use energy, materials and water rationally during the process of manufacturing new products. Development of new products in SMEs on the territory of the Republic of Serbia is burdened by numerous problems among which the most influential ones are: financial flow, poor market estimation, lack of knowledge, lack of ISO 9001 certificate and weak organizational structure. On the bases of the data research we have identified the following problems in small enterprises: individual knowledge, distribution and realization of work tasks, increase of operational expenses caused by bad distribution of work tasks, exceptionally poor communication with consumers.
Keywords: Cybernetic model; Remanufacturing; Small-scale production; Manufacture